Organizational Culture and Employees Performance in the National Agency for Food and Drugs Administration and Control (Nafdac), Nigeria (Global Journal of Management and Business Research, 2014)
The paper discussed organizational culture and employees' performance in the National Agency for Food and Drugs Administration and Control (NAFDAC), Nigeria. It views organizational culture as shared values, beliefs and norms that influence the way employees think, feel and behave in the workplace. It assumes that a positive organizational culture will enhance employees' performance. The research question adderssed the extent of the relationship between organiza-tional culture and increased employees commi-tment/productivity in NAFDAC. The place of study consists of the 6 zonal and 36 state offices of NAFDAC in Nigeria while the duration of study is between February 2013 and January 2014.A descriptive research design was used in executing the study using 420(judgmentally determined) randomly selected NAFDAC employees from its zonal/state offices in Nigeria for questionnaire administration.
Keywords: organizational culture; employees#x2019; commitment; employees#x2019; productivity; NAFDAC